Optimism as the Base of Economic Revival - Eva Andriani; Arifatul Ma'ani; Syovinatus Sholicha (Journal of Social Research, 2022)
Optimism is the most important part in building one's mindset. While mindset is the key to success in achieving all expectations. Economic downturn is not an obstacle for anyone who always faces it with a cool head, even the key to economic revival is in a pattern of heart that is always positive in facing everything. Because in the sunnah of the Apostle positive thingking becomes the highest doctrine, especially in the context of success. Thus, economic revival depends on a commitment to always strive for success.